If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-28-7x=-2(7x+7)
We move all terms to the left:
-28-7x-(-2(7x+7))=0
We calculate terms in parentheses: -(-2(7x+7)), so:We get rid of parentheses
-2(7x+7)
We multiply parentheses
-14x-14
Back to the equation:
-(-14x-14)
-7x+14x+14-28=0
We add all the numbers together, and all the variables
7x-14=0
We move all terms containing x to the left, all other terms to the right
7x=14
x=14/7
x=2
| x/3+34=90 | | 59=9u-4 | | 6x+29=180-3x+124 | | 100*t=8.0811 | | 7(t–74)=98 | | x+134=132 | | 2y/3-1=1 | | 6x-8=3x+65 | | 6y+7=4y+15 | | 2x^2+21x=0 | | 5(z+4)=+5(2−z)= | | 13m-9=17 | | -5n=200 | | -6=-2+x/6 | | P=200+5n | | 1-2x=1+5x+x | | -3=-5t+7 | | -3t+6=6 | | 59=9u–4 | | c+33/4=12/3 | | 20=24–4s | | 13=21-4w | | 28=9+8+c | | 10=21/4*t | | 2(-4+2x)-2(1+6x)=6 | | m/3+5=9 | | 6w+51/2=7 | | -6n+11=-67 | | m3+5=9 | | n-15=6 | | 2x+11=6/4x+33/4 | | 6w+1.5=7 |